Pertanggung Jawaban Tindak Pidana Pelaku Pemerkosaan Sesama Jenis (Homoseksual) Dalam Perspektif Hukum Pidana - Bintoro, Arifah Moerfitria; Simangunsong, Frans (Journal Evidence Of Law, 2023)
Man was made through God in pairs. Sexual desire arises between the developmentof man and woman. There is always a tendency that sexual intercourse when men and women are currently familiar with each other Some surround it illegally, while others surround it secretly. Very not always cases of sexual offense follow the form of what has been mentioned earlier. Humans sometimes engage in sexual relations with other individuals of the same sex, chances are that they happen to be women with women or men with men. Three different types of every sexual orientation are out there: heterosexual, homosexual, and bisexual. Bisexuals express attraction to both sexes, homosexuals represent attraction to the same sex, and heterosexuals summarize attraction to different sexes. While homosexual men are generally referred to as openly gay and homosexual women as lesbians, those who are heterosexual are also known as heterosexuals. In general,while it is true that homosexuality itself is not recognized as unlawful, the laws of the country do not support gays in a broad sense. A person who is a member of an organized homosexual society has no right to marry or adopt. Law No. 1 of 1974, specifically Article1, which defines that marriage is limited to a ceremony between a man and a woman, is a law that expressly deals with sexual orientation or gender identity. The only genders allowed under Indonesian law remain male and female. Homosexuality was not a crime until recently. There are no regulations governing homosexuality when it comes tocommitting sexual crimes Homosexuality is an expression of sexual orientation. To attemptto prevent sexual crimes, the public must be educated honestly so that those with gay preferences have the same possibilities as individuals with the opposite sexual sign of hetenosex. And delay stigmatizing homosexuals for committing sexual crimes or systematically discriminating against them.